2016
DOI: 10.1097/md.0000000000004167
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective effects of renin–angiotensin system inhibitor combined with calcium channel blocker or diuretic in hypertensive patients

Abstract: Objectives:To conduct a meta-analysis of studies comparing the renoprotective effects of angiotensin-converting enzyme inhibitor/angiotensin receptor blocker (ACEI/ARB) combined with either calcium channel blocker (CCB) or diuretic, but not both, in hypertensive patients.Data sources:Pubmed, Embase, Medline, and Cochrane databases were searched to identify randomized controlled trials (RCTs) of blood pressure lowering treatments in patients with hypertension.Study selection:RCTs comparing the renoprotective ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…(Sepehr-Ara et al, 2010; Sepehr-Ara et al, 2011) A meta-analysis concluded that ACEI/ARB plus CCB (including amlodipine) is stronger than ACEI/ARB plus diuretics for maintaining renal function in hypertensive patients. (Cheng et al, 2016) The study by Russo et al found that the renal plasma flow and GFR were increased in the group receiving nifedipine prior to injection of CM (n=30). (Russo et al, 1990) However, some other studies have reported the opposite.…”
Section: Discussionmentioning
confidence: 96%
“…(Sepehr-Ara et al, 2010; Sepehr-Ara et al, 2011) A meta-analysis concluded that ACEI/ARB plus CCB (including amlodipine) is stronger than ACEI/ARB plus diuretics for maintaining renal function in hypertensive patients. (Cheng et al, 2016) The study by Russo et al found that the renal plasma flow and GFR were increased in the group receiving nifedipine prior to injection of CM (n=30). (Russo et al, 1990) However, some other studies have reported the opposite.…”
Section: Discussionmentioning
confidence: 96%
“…Thus, in recent clinical guidelines, eGFR, calculated based on the SCr level and other parameters, is recommended for the estimation of renal function because of its sensitivity and high specificity for one-time measures of renal damage or dysfunction (Qaseem et al, 2013;Stevens and Levin, 2013). Previous studies have demonstrated that angiotensin converting enzyme inhibitors (ACEIs) and ARBs could maintain eGFR during the progress of hypertension (Cheng et al, 2016). Similar to other outcomes, we found that STS and ARB combination is more effective than ARB monotherapy in improving eGFR.…”
Section: Discussionmentioning
confidence: 99%